Pengaruh Model Pembelajaran RADEC Terhadap Penguatan Profil Pelajar Pancasila Bernalar Kritis Siswa Kelas V Sekolah Dasar - fitria, Putri; Hadis, Moch Ludfy; Wahju, Endang (Universitas Islam 45 Bekasi, 2025)
This study aims to determine the impact of the RADEC (Read, Answer, Discuss, Explain, Create) learning model on strengthening the critical reasoning Pancasila learner profile of grade V elementary school students, as well as to see students’ responses to the RADEC model. The research method used is quantitative with a one-shot case study experimental design. Data collection instruments are tests and questionnaires. The test questions were reasoning skills at the C4 level of Bloom’s Taxonomy, namelyvthe ability to analyze information, ideas, and arguments in depth. The results of data analysis showed that the RADEC learning model had a significant effect on strengthening students’ critical reasoning Pancasila learner profile. This is supported by the test results of the the validity of the test (all items are valid with r count > 0.768) and reliability test (Cronbach’s Alpha = 0.507). The Shapiro-Wilk normality test showed the data of pre-test 0. 302 and post-test 0.078 data were normally distributed significance > 0,05. Furthermore, the results of the Paired Sample t-test showed a t value of -13.590 with a significance > 0. 05. Value of -13.590 with a significance (2-tailed) <0.001, identitying a significant difference and increase in post-test scores compared to the pre-test. Students’ response to the learning model is very positive, with an average questionnaire score of 85.5% wich falls into the “very good” category. It is concluded that the RADEC learning model is effective in improving students’ critical reasoning skills and gaining students’ critical thinking skills.